Sealing film, electrode lead wire member, and battery
Patent Information
- Application Number
- JP2026184554
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-05-25
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-16
Smart Images

Figure 2026169373000001_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a sealing film, an electrode lead wire member, and a battery. This application claims priority based on Japanese Patent Application No. 2020-90651 filed in Japan on May 25, 2020, the content of which is incorporated herein by reference in its entirety.
Background Art
[0002] In recent years, secondary batteries such as lithium ion batteries, capacitors, and the like have attracted attention as storage batteries for storing electric energy. A storage battery includes, for example, a battery main body, a storage container that houses the battery main body, and an electrode lead wire connected to the battery main body. The storage container is produced using a laminate for battery exterior that is excellent in waterproofness and light-shielding properties. The laminate for battery exterior is, for example, a laminate in which a base material layer made of polyamide or the like and an aluminum foil are laminated. The electrode lead wire is sealed in the storage container in a state where a portion including one end is drawn out to the outside from the storage container.
[0003] In a storage battery, when water enters the storage container, the water may react with components in the electrolytic solution to generate hydrogen fluoride. Hydrogen fluoride may deteriorate the electrode lead wire and affect the battery life. Therefore, it has been proposed to interpose a sealing film (resin film) between the storage container and the electrode lead wire (see, for example, Patent Document 1). The sealing film adheres the electrode lead wire and the storage container to each other, and suppresses the formation of a gap between the storage container and the electrode lead wire. This makes it difficult for water to enter the inside of the storage container from the outside through the gap.
Prior Art Documents
Patent Documents
[0004]
Patent Document 1
Summary of Invention
Problems to be Solved by the Invention
[0005] The sealing film (hereinafter referred to as the sealing film) should preferably have high adhesive strength to the electrode lead wires and the containment container. Furthermore, since the sealing film may come into contact with the electrolyte inside the containment container, resistance to the electrolyte is required. In other words, the sealing film must possess the following three characteristics: (i) Adhesion strength to the electrode lead wire (first substrate). (ii) Adhesion strength to the containment container (second substrate). (iii) Resistance to electrolytes.
[0006] However, the three characteristics (i) to (iii) are in a trade-off relationship, and it was not easy to improve any of them.
[0007] One aspect of the present invention aims to provide a sealing film, an electrode lead wire member, and a battery that have high adhesive strength to a first substrate and a second substrate, and resistance to electrolyte. [Means for solving the problem]
[0008] To solve the above problems, one aspect of the present invention includes the following aspects.
[0009] [1] A sealing film for sealing between a first metal substrate and a second substrate, comprising: a first adhesive layer mainly containing an acid-modified polyolefin and adhering to the first substrate; a second adhesive layer mainly containing a polyolefin and adhering to the second substrate; and a base layer provided between the first adhesive layer and the second adhesive layer, wherein the thickness of the first adhesive layer is 25 to 70, with the total thickness of the sealing film being 100; the thickness of the base layer is 25 to 70, with the total thickness of the sealing film being 100; and the thickness of the second adhesive layer is 5 to 50, with the total thickness of the sealing film being 100.
[0010] [2] The sealing film according to [1], wherein the melting point of the resin constituting the base layer is higher than the melting point of the resin constituting the first adhesive layer or the second adhesive layer.
[0011] [3] The sealing film according to [1] or [2], wherein the polyolefin constituting the second adhesive layer is an acid-modified polyolefin.
[0012] [4] The sealing film according to any one of [1] to [3], wherein the melting point of the resin constituting the base layer is 150°C or more and 170°C or less, and the melting point of the resin constituting the second adhesive layer is 110°C or more and 150°C or less.
[0013] [5] The sealing film according to any one of [1] to [4], wherein the melting point of the resin constituting the first adhesive layer is 110°C or higher and 150°C or lower.
[0014] An electrode lead wire member comprising a sealing film described in any one of [6][1] to [5], and the first substrate which is an electrode lead wire extending in one direction.
[0015] A battery comprising an electrode lead wire member as described in [7][6], a battery body to which the electrode lead wire is connected, and the second base body which is a housing container for housing the battery body. [Effects of the Invention]
[0016] According to one aspect of the present invention, a sealing film, an electrode lead wire member, and a battery can be provided that have high adhesive strength to a first substrate and a second substrate, and resistance to electrolyte. [Brief explanation of the drawing]
[0017] [Figure 1] This is a schematic cross-sectional view showing the sealing film of the embodiment. [Figure 2] This is a schematic perspective view showing the electrode lead wire member of the embodiment. [Figure 3] This is a schematic perspective view showing a battery according to an embodiment. [Figure 4] This is a cross-sectional view taken along the line I-I in Figure 3 as viewed in the direction of the arrows. [Mode for Carrying Out the Invention]
[0018] Hereinafter, the sealing film, the electrode lead wire member, and the battery according to the embodiment will be described with reference to Figures 1 to 4. Note that in the drawings, the dimensions, ratios, and the like of the constituent elements may differ from the actual values.
[0019] <Sealing Film> Figure 1 is a schematic cross-sectional view showing the sealing film 1 of the embodiment. Figure 2 is a schematic perspective view showing the electrode lead wire member 10 of the embodiment.
[0020] As shown in Figure 2, the electrode lead wire member 10 includes an electrode lead wire 11 and the sealing film 1. The electrode lead wire 11 is an example of the "first base body". As shown in Figure 1, the sealing film 1 includes a first adhesive layer 2, a second adhesive layer 3, and a base material layer 4.
[0021] [First Adhesive Layer] The first adhesive layer 2 is a layer that is fused (adhered) to the electrode lead wire 11 (see Figure 2) by heating or pressurization. The surface of the first adhesive layer 2 is one surface 1a of the sealing film 1. The first adhesive layer 2 is composed of a resin.
[0022] The first adhesive layer 2 mainly contains an acid-modified polyolefin. The expression that the first adhesive layer 2 "mainly contains an acid-modified polyolefin" means that the content ratio of the acid-modified polyolefin is the highest among the resins constituting the first adhesive layer 2. The first adhesive layer 2 preferably contains the acid-modified polyolefin in an amount of 50% by mass or more (preferably, contains the acid-modified polyolefin in an amount exceeding 50% by mass) relative to the total amount of the first adhesive layer 2. The first adhesive layer 2 preferably contains the acid-modified polyolefin in an amount of 80% by mass or more relative to the total amount of the first adhesive layer 2.
[0023] The first adhesive layer 2 may contain 100% by mass of the acid-modified polyolefin relative to the total amount of the first adhesive layer 2. In one embodiment of the present invention, the first adhesive layer 2 "mainly contains acid-modified polyolefin" means that the first adhesive layer 2 contains 80% by mass or more and 100% by mass or less of acid-modified polyolefin with respect to the total amount of the first adhesive layer 2.
[0024] Examples of polyolefins constituting the first adhesive layer 2 include polypropylene, polyethylene, poly-1-butene, and polyisobutylene. Among these, polypropylene is preferred due to its excellent flexibility. Hereafter, polypropylene may be abbreviated as "PP".
[0025] Polyolefins may also be copolymers of propylene and ethylene (propylene-ethylene copolymers). Among these, random copolymers of propylene and ethylene are preferred. Polyolefins may also be copolymers of propylene and olefin monomers. Examples of olefin monomers include 1-butene, isobutylene, and 1-hexene.
[0026] Acid-modified polyolefins are polyolefin resins modified with unsaturated carboxylic acids or their derivatives, and are resins having acidic functional groups such as carboxyl groups or carboxylic anhydride groups within the polyolefin resin. Acid-modified polyolefins can be obtained by modifying polyolefin resins with unsaturated carboxylic acids or their derivatives, or by copolymerizing acid-functional group-containing monomers with olefins. The use of acid-modified polyolefins can improve the adhesion of the first adhesive layer 2 to the electrode lead wire 11 (see Figure 2).
[0027] As an acid-modified polyolefin, acid-modified polypropylene (acid-modified PP) is preferred due to its excellent heat resistance. Acid-modified PP is, for example, a polymer obtained by graft copolymerizing a monomer having a carboxyl group onto polypropylene or a propylene-ethylene copolymer. Examples of monomers having a carboxyl group include unsaturated carboxylic acids such as acrylic acid and methacrylic acid; unsaturated carboxylic acid esters such as ethyl acrylate; and acid anhydrides such as maleic anhydride.
[0028] Acid-modified PP includes ionomers obtained by neutralizing the carboxylic acid groups of an acid-modified polymer of polypropylene or an acid-modified polymer of propylene-ethylene copolymer with metal hydroxides, alkoxides, lower fatty acid salts, etc. The acid group in acid-modified PP is preferably a maleic anhydride group. In other words, maleic anhydride-modified PP is preferred as the acid-modified PP.
[0029] The melting point of the resin constituting the first adhesive layer 2 is preferably 110°C or higher and 150°C or lower. If the melting point of the resin constituting the first adhesive layer 2 is 110°C or higher, the first adhesive layer 2 is less likely to become excessively thin during heat bonding, making it easier to ensure adhesive strength. If the melting point of the resin constituting the first adhesive layer 2 is 150°C or lower, the resin flows more easily during heat bonding, allowing the resin to sufficiently wrap around the electrode lead wire 11, making it easier to seal the entire circumference of the electrode lead wire 11.
[0030] If the "resin constituting the first adhesive layer 2" is a polymer alloy of two or more resins, then the "melting point of the resin constituting the first adhesive layer 2" refers to the melting point of the polymer alloy constituting the first adhesive layer 2.
[0031] In the first adhesive layer 2, optional components other than polyolefins include known additives such as stabilizers, antistatic agents, and colorants.
[0032] The thickness of the first adhesive layer 2 is set to be between 25% and 70%, with the total thickness of the sealing film 1 being 100%. In other words, the thickness of the first adhesive layer 2 is between 25% and 70% of the total thickness of the sealing film 1. The ratio of the layer thickness to the total thickness of the sealing film 1, which is set to 100%, is called the "thickness ratio."
[0033] If the thickness ratio of the first adhesive layer 2 is 25 or more, sufficient adhesive strength between the first adhesive layer 2 and the electrode lead wire 11 can be ensured. If the thickness ratio of the first adhesive layer 2 is 70 or less, sufficient thickness can be provided to the second adhesive layer 3 and the base material layer 4. Therefore, the electrolyte resistance of the sealing film 1 can not be reduced, and the adhesive strength between the second adhesive layer 3 and the containment container can be increased. Note that "electrolyte resistance" refers to resistance to electrolyte.
[0034] [Second adhesive layer] The second adhesive layer 3 is a layer that fuses (adheres) to the containment container by, for example, heating or pressurizing. The containment container will be described later. The surface of the second adhesive layer 3 is the other surface 1b of the sealing film 1. The second adhesive layer 3 is made of resin.
[0035] The second adhesive layer 3 mainly contains polyolefin. "Mainly containing polyolefin" means that polyolefin has the highest content among the resins constituting the second adhesive layer 3. Preferably, the second adhesive layer 3 contains 50% by mass or more of polyolefin relative to the total amount of the second adhesive layer 3 (preferably, more than 50% by mass of polyolefin). Preferably, the second adhesive layer 3 contains 80% by mass or more of polyolefin relative to the total amount of the second adhesive layer 3.
[0036] The second adhesive layer 3 may contain 100% by mass of acid-modified polyolefin relative to the total amount of the second adhesive layer 3. In one embodiment of the present invention, the second adhesive layer 3 "mainly contains acid-modified polyolefin" means that the second adhesive layer 3 contains 80% by mass or more and 100% by mass or less of acid-modified polyolefin relative to the total amount of the second adhesive layer 3.
[0037] Examples of polyolefins constituting the second adhesive layer 3 include polypropylene (PP), polyethylene, poly-1-butene, and polyisobutylene. Among these, PP is preferred due to its excellent flexibility.
[0038] Polyolefins may also be copolymers of propylene and ethylene (propylene-ethylene copolymers). Among these, random copolymers of propylene and ethylene are preferred. Polyolefins may also be copolymers of propylene and olefin monomers (for example, random copolymers). Examples of olefin monomers include 1-butene, isobutylene, and 1-hexene.
[0039] The polyolefin constituting the second adhesive layer 3 may be an acid-modified polyolefin. As the acid-modified polyolefin, acid-modified PP is preferred due to its excellent heat resistance. As the acid-modified PP, the acid-modified PP exemplified as the material for the first adhesive layer 2 described above is preferably used. As the acid-modified PP, a polymer obtained by acid-modifying a random copolymer of propylene and ethylene is preferred due to its excellent flexibility. By using an acid-modified polyolefin, the adhesion of the second adhesive layer 3 to the container can be improved.
[0040] The second adhesive layer 3 may contain both acid-modified PP and acid-modified polyethylene. When the second adhesive layer 3 contains both acid-modified PP and acid-modified polyethylene, the melting point of the second adhesive layer 3 can be lowered, and the heating temperature when fusing the second adhesive layer 3 can be reduced, thereby suppressing the deterioration of the first adhesive layer 2.
[0041] The melting point of the resin constituting the second adhesive layer 3 is preferably 110°C to 150°C. If the melting point of the resin constituting the second adhesive layer 3 is 110°C or higher, the second adhesive layer 3 is less likely to become excessively thin during heat bonding, making it easier to ensure adhesive strength. If the melting point of the resin constituting the second adhesive layer 3 is 150°C or lower, the resin flows more easily during heat bonding, making it easier to seal the space between the containment container and the electrode lead wire 11.
[0042] If the "resin constituting the second adhesive layer 3" is a polymer alloy of two or more resins, then the "melting point of the resin constituting the second adhesive layer 3" refers to the melting point of the polymer alloy constituting the second adhesive layer 3.
[0043] In the second adhesive layer 3, optional components other than acid-modified polyolefins include known additives such as stabilizers, antistatic agents, and colorants.
[0044] The thickness (thickness ratio) of the second adhesive layer 3 is set to be between 5% and 50%, with the total thickness of the sealing film 1 being 100%. In other words, the thickness of the second adhesive layer 3 is between 5% and 50% of the total thickness of the sealing film 1.
[0045] If the thickness ratio of the second adhesive layer 3 is 5 or more, sufficient adhesive strength between the second adhesive layer 3 and the containment container can be ensured. If the thickness ratio of the second adhesive layer 3 is 50 or less, sufficient thickness can be provided to the first adhesive layer 2 and the base material layer 4. Therefore, the electrolyte resistance of the sealing film 1 can not be reduced, and the adhesive strength between the first adhesive layer 2 and the electrode lead wire 11 can be increased.
[0046] [Base material layer] The base layer 4 is interposed between the first adhesive layer 2 and the second adhesive layer 3. The base layer 4 is made of resin.
[0047] The base layer 4 mainly contains, for example, polyolefin. "Mainly containing polyolefin" means that polyolefin has the highest content among the resins constituting the base layer 4. Preferably, the base layer 4 contains 50% by mass or more of polyolefin relative to the total amount of the base layer 4 (preferably, more than 50% by mass of polyolefin relative to the total amount of the base layer 4). Preferably, the base layer 4 contains 80% by mass or more of polyolefin relative to the total amount of the base layer 4.
[0048] The base layer 4 may contain 100% by mass of acid-modified polyolefin relative to the total amount of the base layer 4. In one embodiment of the present invention, the statement that the base layer 4 "mainly contains acid-modified polyolefin" means that the base layer 4 contains 80% by mass or more and 100% by mass or less of acid-modified polyolefin relative to the total amount of the base layer 4.
[0049] Examples of polyolefins constituting the base layer 4 include polypropylene (PP), polyethylene, poly-1-butene, and polyisobutylene. Among these, PP is preferred due to its excellent flexibility.
[0050] The polyolefin constituting the base layer 4 may be a homopolymer of one type of olefin, or a copolymer of two or more types of olefins. An example of a homopolymer is a homopolymer of propylene alone (homoPP). An example of a copolymer is a copolymer of propylene and an olefin monomer (ethylene, 1-butene, isobutylene, 1-hexene, etc.), such as a propylene-ethylene copolymer.
[0051] As the polyolefin constituting the base layer 4, ICP (impact copolymer) is preferred. The ICP has a phase-separated structure having a first phase and a second phase, for example, a sea-island structure. The sea-island structure is a structure in which multiple second phases corresponding to "islands" are dispersed in a first phase corresponding to the "sea".
[0052] The first phase is composed of homopolymers of olefin monomers such as propylene and ethylene. The second phase is composed of polymers different from the homopolymers that make up the first phase. The second phase includes polymers of olefin monomers such as propylene and ethylene, such as ethylene-propylene rubber (EPR). The second phase is composed of a main phase and a surface layer covering the surface of the main phase. The main phase is composed of polyethylene, for example. The surface layer is composed of EPR, for example.
[0053] ICP in which the homopolymer constituting the first phase is homo-PP is called polypropylene ICP or polypropylene dispersion. ICP in which the homopolymer constituting the first phase is homo-PP is also known as block PP. ICP is also called heterophasic copolymer or block copolymer.
[0054] The constituent materials of the base layer are not particularly limited, and resins other than polyolefins (for example, fluororesins such as polychlorotrifluoroethylene) may be used.
[0055] The thickness (thickness ratio) of the base layer 4 is set to be between 25 and 70, with the total thickness of the sealing film 1 being 100. In other words, the thickness of the base layer 4 is between 25 and 70 of the total thickness of the sealing film 1.
[0056] When the thickness ratio of the base layer 4 is 25 or more, sufficient electrolyte resistance of the sealing film 1 can be ensured. In addition, when the thickness ratio of the base layer 4 is 25 or more, the resin does not flow too much and is more likely to exhibit the necessary fluidity during compression.
[0057] When the thickness ratio of the base material layer 4 is 70 or less, sufficient thickness can be provided to the first adhesive layer 2 and the second adhesive layer 3. As a result, the adhesive strength between the first adhesive layer 2 and the electrode lead wire 11, and the adhesive strength between the second adhesive layer 3 and the containment container can both be increased. Furthermore, when the thickness ratio of the base material layer 4 is 70 or less, the fluidity of the resin does not decrease, and the fluidity of the resin during heat-press bonding can be kept within an appropriate range.
[0058] The melting point of the resin constituting the base layer 4 is preferably 150°C to 170°C. If the melting point of the resin constituting the base layer 4 is 150°C or higher, it is easier to ensure the electrolyte resistance of the sealing film 1. Furthermore, heat resistance can be imparted to the sealing film 1. If the melting point of the resin constituting the base layer 4 is 170°C or lower, flexibility can be given to the sealing film 1. As a result, gaps are less likely to form between the electrode lead wires 11 and the containment container and the sealing film 1.
[0059] The melting point M4 of the resin constituting the base layer 4 is higher than the melting point M2 of the resin constituting the first adhesive layer 2, or the melting point M3 of the resin constituting the second adhesive layer 3. That is, the melting point M4 is higher than either the melting point M2 or the melting point M3. It is desirable that the melting point M4 is higher than either the melting point M2 or the melting point M3. In one embodiment of the present invention, it is desirable that the melting point M4 is higher than at least one of the melting points M2 and the melting point M3.
[0060] If the melting point M4 is higher than the melting point M2, it becomes easier to ensure the electrolyte resistance of the sealing film 1 without reducing the adhesive strength between the first adhesive layer 2 and the electrode lead wire 11. If the melting point M4 is higher than the melting point M3, it becomes easier to ensure the electrolyte resistance of the sealing film 1 without reducing the adhesive strength between the second adhesive layer 3 and the containment container. If the melting point M4 is higher than either or both of the melting points M2 or M3, there is also the advantage that it is easier to impart heat resistance to the sealing film 1.
[0061] <Electrode lead wire component> As shown in Figure 2, the electrode lead wire member 10 has an electrode lead wire 11 and a pair of sealing films 1. The pair of sealing films 1 are arranged with their first adhesive layers 2 facing each other. The pair of sealing films 1 sandwich the electrode lead wire 11. Each of the pair of sealing films 1 contacts a region corresponding to one side and the other side of the electrode lead wire 11. Therefore, the pair of sealing films 1 as a whole are in contact with the entire circumference of the electrode lead wire 11.
[0062] The electrode lead wire 11 has a lead wire body 111 and a surface treatment layer 112. The electrode lead wire 11 extends linearly in one direction. The electrode lead wire 11 is made of metal.
[0063] The electrode lead wire 11 is conductive. The electrode lead wire 11 is electrically connected to the lithium-ion battery 30 (see Figure 3). The electrode lead wire 11 conducts power between the lithium-ion battery 30 and an external device. As the material for the lead wire body 111, known metals such as aluminum, copper, nickel, iron, gold, platinum, and various alloys can be used. Among these, aluminum or copper are preferred because they have excellent conductivity and are cost-effective.
[0064] The lead wire body 111 may have a nickel-plated surface. The nickel plating of the lead wire body 111 may be formed by electroplating using a Watt bath mainly composed of nickel sulfate, nickel chloride, boric acid, etc. It is preferable to perform the nickel plating of the lead wire body 111 using a nickel sulfamate plating bath mainly composed of nickel sulfamate and boric acid. The plating film formed by this method has excellent flexibility, making the plating film less prone to cracking. The lead wire body 111 is preferably made of an aluminum plate or a nickel-plated copper plate.
[0065] The surface treatment layer 112 is formed on the surface of the lead wire body 111. The surface treatment layer 112 has corrosion resistance. "Corrosion resistance" refers to the property of being resistant to corrosion caused by the electrolyte inside the battery. Examples of the surface treatment layer 112 include acid-resistant coatings made from phosphates, chromates, fluorides, or triazinethiol compounds. The acid-resistant coating can be formed by applying a chemical conversion treatment to the lead wire body 111.
[0066] In Figure 2, the surface treatment layer 112 is formed on a portion of the surface of the lead wire body 111, but the surface treatment layer 112 may be formed over the entire surface of the lead wire body 111. Note that the electrode lead wire does not necessarily need to have a surface treatment layer formed on it.
[0067] Because the thickness ratio of the first adhesive layer 2, the base layer 4, and the second adhesive layer 3 of the sealing film 1 is within the aforementioned range, it has good adhesive strength to the electrode lead wires 11 and the housing container, and is resistant to the electrolyte. Because the sealing film 1 has good adhesive strength to the electrode lead wires 11 and the housing container, it can prevent water from entering the inside of the housing container from the outside. Because the sealing film 1 is resistant to the electrolyte, it is possible to realize a battery 100 that is less prone to degradation and highly reliable.
[0068] The sealing film 1 contains an acid-modified polyolefin as the material for forming the first adhesive layer 2. Therefore, the first adhesive layer 2 readily heat-fusses to the electrode lead wire 11, and the interface between the electrode lead wire 11 and the sealing film 1 can be sealed. Thus, it is possible to suppress water from entering the container from the outside.
[0069] The sealing film 1 contains an acid-modified polyolefin as the material for forming the second adhesive layer 3. Therefore, the second adhesive layer 3 readily heat-seals with the resin material constituting the battery housing, and the interface between the housing and the sealing film 1 is easily sealed.
[0070] Since the electrode lead wire member 10 is equipped with a sealing film 1, it is possible to prevent water from entering the inside of the containment container from the outside.
[0071] <Battery> Figure 3 is a schematic perspective view showing the battery 100 of the embodiment. As shown in Figure 3, the battery 100 comprises the electrode lead wire member 10 described above, a housing container 20, and a lithium-ion battery 30 (battery body).
[0072] The containment container 20 has a container body 21 and a lid 22. The containment container 20 is an example of the "second substrate". The container body 21 has a molded portion 21a that forms a recess for housing the lithium-ion battery 30. The container body 21 is obtained by drawing a laminate for battery casing. The lid 22 is made of a laminate for battery casing and has the same planar area as the container body 21. The laminate for battery casing will be described later. The container 20 is formed by overlapping the container body 21 and the lid 22 and heat-sealing the peripheral edge 25.
[0073] Figure 4 is a cross-sectional view taken along line segment II in Figure 3. As shown in Figure 4, the laminate for the battery casing, which is the constituent material of the container body 21 and the lid 22, is a laminate in which a first film substrate 201, a second film substrate 202, a metal foil 203, and a sealant layer 204 are laminated in this order.
[0074] The resins constituting the first film substrate 201 and the second film substrate 202 are not particularly limited, but polyamide, polyethylene terephthalate (PET), phenolic resin, polypropylene, etc. are preferred. As the metal foil 203, aluminum foil, stainless steel foil, copper foil, iron foil, etc. are preferred.
[0075] The sealant layer 204 is heat-fused to the second adhesive layer 3 of the sealing film 1. The resin constituting the sealant layer 204 is selected to be fused to the sealing film 1. Examples of resins constituting the sealant layer 204 include polypropylene resins and polyethylene resins. As polypropylene resins, polypropylene homopolymers, copolymers of propylene and ethylene, etc., can be used. As polyethylene resins, low-density polyethylene, linear low-density polyethylene, etc., may be used.
[0076] As shown in Figures 3 and 4, in the battery 100, the electrode lead wires 11 are drawn out from the lithium-ion battery 30 inside the housing 20 (inside the molded part 21a) to the outside of the housing 20. The electrode lead wires 11 are fused to the sealant layer 204 of the housing 20 via the sealing film 1.
[0077] In the battery 100, since the electrode lead wire member 10 has the aforementioned sealing film 1, it is possible to suppress water from entering the housing container from the outside. Therefore, a battery 100 that is less prone to degradation and highly reliable can be realized.
[0078] Preferred embodiments of the present invention have been described above with reference to the attached drawings, but the present invention is not limited to these examples. The shapes and combinations of the constituent members shown in the above examples are just examples, and can be modified in various ways based on design requirements, etc., without departing from the spirit of the present invention. For example, the first adhesive layer and the second adhesive layer may contain resins other than polyolefins. [Examples]
[0079] The present invention will be described below with reference to examples, but the present invention is not limited to these examples.
[0080] <Preparation of sealing film> A sealing film was prepared by laminating a first adhesive layer, a substrate layer, and a second adhesive layer in that order as follows: The resins that would be the raw materials for each layer were heated and melted separately, and a laminate was obtained by simultaneously forming a multilayer film using an extruder capable of simultaneous multilayer extrusion molding. By cutting this laminate to a predetermined size, the sealing films of each example and comparative example were obtained. The sealing films were formed in a strip shape (width 15 mm, thickness 100 μm).
[0081] The constituent materials of the first adhesive layer, the substrate layer, and the second adhesive layer are as follows: First adhesive layer: Maleic anhydride-modified polypropylene (melting point 140°C) Base layer: Polypropylene ICP (melting point 161℃) Second adhesive layer: Random copolymer of propylene and ethylene (melting point 140°C)
[0082] The melting point M4 of the polypropylene ICP resin that constitutes the base layer is higher than the melting point M2 of the resin that constitutes the first adhesive layer and the melting point M3 of the resin that constitutes the second adhesive layer.
[0083] Maleic anhydride-modified polypropylene is a polymer obtained by graft polymerization of maleic anhydride onto a random copolymer of propylene and ethylene. Polypropylene ICP has a structure in which the second phase is dispersed within the first phase (sea-island structure). The first phase is composed of homo-PP. The second phase contains ethylene propylene rubber and polyethylene. Polypropylene ICP is a mixture containing PP, ethylene propylene rubber, and polyethylene.
[0084] <Fabrication of electrode lead wires> An electrode lead wire was fabricated, comprising a lead wire body and a surface treatment layer formed on the surface of the lead wire body. A rectangular nickel-plated copper foil measuring 45 mm in width and 52 mm in length was used as the lead wire body.
[0085] <Fabrication of laminated structures for battery casings> A laminate for battery casing was obtained by dry laminating a 12 μm thick PET film, a 15 μm thick nylon film, a 40 μm thick aluminum foil, and an 80 μm thick PP film.
[0086] PET film, nylon film, aluminum foil, and PP film correspond to the first film substrate 201, second film substrate 202, metal foil 203, and sealant layer 204, respectively (see Figure 4).
[0087] <Measurement of adhesive strength to electrode lead wires> The adhesive strength of the sealing film to the electrode lead wires was measured as follows. A laminate was obtained by overlapping a sealing film and electrode lead wires and bonding them together by heat sealing. The resulting laminate was then cut into strips (10 mm wide x 120 mm long) to obtain a sample for measurement. The heat sealing conditions were 180°C, 0.5 MPa, and 10 seconds.
[0088] For this sample, the 180-degree peel strength was measured using a testing machine (a desktop precision universal testing machine manufactured by Shimadzu Corporation: Autograph AGS-500NX) as follows.
[0089] The end of the sealing film and the end of the electrode lead wire were gripped by the gripping part of the testing machine, and the sealing film was peeled away from the electrode lead wire so that it was peeled off at a 180-degree angle. The peeling speed was set to 50 mm / min.
[0090] A peel strength of 10 N / 10 mm or higher was judged as "Good" (OK), indicating high adhesive strength to the electrode lead wire. A peel strength of less than 10 N / 10 mm was judged as "Weak" (NG), indicating low adhesive strength to the electrode lead wire. The results are shown in Table 1.
[0091] <Electrolyte resistance test> The resistance of the sealing film to the electrolyte was evaluated as follows. A packaging bag was prepared using a laminate for battery casings, and an electrolyte solution containing 1.0 mol / liter of LiPF6 (DMC:EMC:EC=4:3:3) was placed inside. 0.2% by mass (2000 ppm) of pure water was added to the electrolyte solution.
[0092] The sample for measurement, prepared in the same manner as described in "Measurement of Adhesion Strength to Electrode Lead Wires" above, was placed in this packaging bag and immersed in the electrolyte solution. After storing the packaging bag containing the sample for measurement in an 85°C oven for 7 days, the peel strength was measured in the same manner as described in "Measurement of Adhesion Strength to Electrode Lead Wires".
[0093] A peel strength of 10 N / 10 mm or higher was judged as "Good" (OK), indicating high resistance to the electrolyte. A peel strength of less than 10 N / 10 mm was judged as "Poor" (NG), indicating low resistance to the electrolyte. The results are shown in Table 1.
[0094] <Measurement of adhesive strength to the container> The adhesive strength of the sealing film to the container was measured as follows. The electrode lead wires, with their heat-sealed sealing film, were placed on top of the laminate for the battery casing and bonded together by heat sealing to obtain a sample for measurement. The heat sealing conditions were 200°C, 0.3 MPa, and 3.5 seconds.
[0095] For this test specimen, the end of the battery outer layer laminate and the end of the electrode lead wire were gripped by the gripping part of the testing machine, and the battery outer layer laminate was peeled away from the electrode lead wire so that it was peeled off at a 180-degree angle. The peeling speed was set to 50 mm / min.
[0096] A peel strength of 100 N / 15 mm or higher was judged as "Good" (OK), indicating high adhesive strength to the container. A peel strength of less than 100 N / 15 mm was judged as "Weak" (NG), indicating low adhesive strength to the container. The results are shown in Table 1.
[0097] [Table 1]
[0098] As shown in Table 1, in Comparative Example 1, the adhesive strength to the containment container is thought to be low because the second adhesive layer is thin. In Comparative Examples 2, 4, and 5, the adhesive strength to the electrode lead wires is thought to be low because the first adhesive layer is thin. In Comparative Examples 3 and 6, the electrolyte resistance is thought to be low because the substrate layer is thin.
[0099] In contrast, Examples 1 to 4 showed high adhesive strength to the electrode lead wires and housing containers, as well as resistance to the electrolyte. [Explanation of Symbols]
[0100] 1...Sealing film, 2...First adhesive layer, 3...Second adhesive layer, 4...Base layer, 10...Electrode lead wire component, 11...Electrode lead wire (first base), 20...Housing container (second base), 30...Lithium-ion battery (battery body), 100...Battery.
Claims
1. A sealing film that seals the space between a first metal substrate and a second substrate, A first adhesive layer mainly comprising an acid-modified polyolefin, which adheres to the first substrate, A second adhesive layer mainly containing polyolefin and adhering to the second substrate, A substrate layer provided between the first adhesive layer and the second adhesive layer, The resin constituting the aforementioned substrate layer consists of a copolymer of two or more olefins, or ICP (impact copolymer). The thickness of the first adhesive layer is 25 to 70, with the total thickness of the sealing film being 100. The thickness of the substrate layer is 25 to 70, with the total thickness of the sealing film being 100. A sealing film in which the thickness of the second adhesive layer is 5 to 15, with the total thickness of the sealing film being 100.
2. The sealing film according to claim 1, wherein the second adhesive layer mainly comprises an acid-modified polyolefin.
3. The sealing film according to claim 1 or 2, wherein the resin constituting the base layer is made of ICP.
4. The sealing film according to any one of claims 1 to 3, wherein the melting point of the resin constituting the base layer is higher than the melting point of the resin constituting the first adhesive layer or the second adhesive layer.
5. The melting point of the resin constituting the base layer is 150°C or higher and 170°C or lower. The sealing film according to any one of claims 1 to 4, wherein the melting point of the resin constituting the second adhesive layer is 110°C or higher and 150°C or lower.
6. The sealing film according to any one of claims 1 to 5, wherein the melting point of the resin constituting the first adhesive layer is 110°C or higher and 150°C or lower.
7. A sealing film according to any one of claims 1 to 6, An electrode lead wire member comprising a first base body which is an electrode lead wire extending in one direction, and
8. The electrode lead wire member according to claim 7, The battery body to which the electrode lead wire member is connected, A battery comprising a second base body which is a housing container for housing the battery body.
Citation Information
Patent Citations
Lead member
JP2017073200A